PENGARUH KEPEMIMPINAN DAN REWARD TERHADAP PEGAWAI PADA UPTD PUSKESMAS MANDREHE - Kelvin Sang Putra Waruwu (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
This research aims to determine the influence of leadership and appreciation on employee performance at the Mandrehe Public Health Center UPTD. Using an associative quantitative research approach, this research uses multiple linear regression analysis to evaluate data. This research covers a population of 40 employees, with a sampling method of saturated samples with the same number. Primary data is collected directly from respondents through questionnaires. The results of the analysis show that leadership and rewards have a partially significant influence on employee performance. In addition, these factors collectively have a significant and positive influence on performance. To improve employee performance, leaders must better address employee weaknesses and focus on increasing motivation through rewards. It is recommended that the leadership at UPTD Puskesmas Mandrehe pay more attention to motivational incentives to boost employee performance.